2020
DOI: 10.3310/hta24040
|View full text |Cite
|
Sign up to set email alerts
|

Group cognitive rehabilitation to reduce the psychological impact of multiple sclerosis on quality of life: the CRAMMS RCT

Abstract: Background People with multiple sclerosis have problems with memory and attention. The effectiveness of cognitive rehabilitation has not been established. Objectives The objectives were to assess the clinical effectiveness and cost-effectiveness of a cognitive rehabilitation programme for people with multiple sclerosis. Design This was a multicentre, randomis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 177 publications
0
28
0
Order By: Relevance
“…Prior studies have used quality of life measures as their primary outcome measure with mixed results. [7][8][9][10] Notably these studies used group cognitive rehabilitation sessions rather than individual therapy sessions. The authors noted a need for additional studies to see if the benefit identified in some of the studies was due to the supportive group setting rather than any cognitive retraining or adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…Prior studies have used quality of life measures as their primary outcome measure with mixed results. [7][8][9][10] Notably these studies used group cognitive rehabilitation sessions rather than individual therapy sessions. The authors noted a need for additional studies to see if the benefit identified in some of the studies was due to the supportive group setting rather than any cognitive retraining or adaptation.…”
Section: Resultsmentioning
confidence: 99%
“…The beneficial effect on mood could be explained considering that participants in the intervention group were less distressed by their memory problems as a result of the memory rehabilitation or due to the social interaction in a group mode. 33 In a multicenter study, Lincoln et al 55 assessed the clinical effectiveness and cost-effectiveness of a CR program for PwMS compared to a usual care intervention. Although both groups showed no differences in quality of life after one year, those who received CR had fewer memory problems in daily life and reported better mood than those who received only their usual clinical care.…”
Section: Treatment Modes: Individual Versus Groupmentioning
confidence: 99%
“…In a multicenter study, Lincoln et al 55 assessed the clinical effectiveness and cost-effectiveness of a CR program for PwMS compared to a usual care intervention. Although both groups showed no differences in quality of life after one year, those who received CR had fewer memory problems in daily life and reported better mood than those who received only their usual clinical care.…”
Section: Treatment Modes: Individual Versus Groupmentioning
confidence: 99%
“…In nonpharmacological treatment, there are specific interventions aimed at physical rehabilitation such as electro-stimulation or Proprioceptive Neuromuscular Facilitation (PNF) [ 15 ]; there are also interventions to maintain daily life skills and others aimed at psychological or cognitive rehabilitation with the participation of occupational therapist [ 11 , 13 ]. Regarding cognitive intervention, Lincoln et al, carried out a comparative study based on attention and memory which resulted in an improvement in memory and lifestyle in the experimental group compared to the control group [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In nonpharmacologi-cal treatment, there are specific interventions aimed at physical rehabilitation such as electro-stimulation or Proprioceptive Neuromuscular Facilitation (PNF) [15]; there are also interventions to maintain daily life skills and others aimed at psychological or cognitive rehabilitation with the participation of occupational therapist [11,13]. Regarding cognitive intervention, Lincoln et al, carried out a comparative study based on attention and memory which resulted in an improvement in memory and lifestyle in the experimental group compared to the control group [16]. Some previous occupational therapy studies have proposed psychosocial promotion interventions [17,18] such as the Community Reintegration for Socially Isolated Patients (CRISP) occupation-based intervention, which used education and self-management strategies in MS patients, performing socializing and recreation activities to improve self-efficacy and to reduce perceptions of loneliness [18].…”
Section: Introductionmentioning
confidence: 99%